Comparing Loop and Divided Colostomy for Anorectal Malformation: A Systematic Review and Meta-Analysis - Gonca Gerçela; Mustafa Azizoglu; Esra Karakas; Toni Risteski; Maria Escolino; Luis De La Torre (Elsevier, 2025)
Introduction: The optimal type of colostomy for patients with anorectal malformations (ARM) remains unclear. We conducted a systematic review and meta-analysis to compare the clinical outcomes of loop colostomies (LC) versus divided colostomies (DC) in patients with ARM. Methods: After review registration (PROSPERO: CRD42024513335), we searched multiple databases for comparative studies on LCs and DCs in patients with ARMs. Gray literature was sought. The complications examined included stoma prolapse, urinary tract infection (UTI), skin excoriation, stoma retraction, parastomal hernia, wound infection rate, and stoma stricture. Three reviewers independently assessed the eligibility and quality of the included studies. Meta-analysis of selected complications was performed using Revman 5.4, with p < 0.05 considered significant. Results: Eleven studies were included in the analysis, incorporating a total of 2550 neonates with ARMs, of which 1147 underwent LCs and 1403 underwent DCs. The meta-analysis revealed no significant differences between the two groups in the incidence of stoma prolapse (OR: 1.55, 95 % CI: 0.63 to 3.79; p = 0.34), UTIs (OR: 1.78, 95 % CI: 0.50 to 6.36; p = 0.38), skin excoriation (OR: 1.26, 95 % CI: 0.68 to 2.34; p = 0.46), stoma retraction (OR: 0.79, 95 % CI: 0.09 to 6.64; p = 0.83), parastomal hernia (OR: 0.99, 95 % CI: 0.22 to 4.48; p = 0.99), wound infection (OR: 0.35, 95 % CI: 0.10 to 1.20; p = 0.10), and stoma stricture (OR: 0.70, 95 % CI: 0.22 to 2.18; p = 0.53). Conclusions: The findings suggest that LCs and DCs are viable options for fecal diversion, presenting similar risks and benefits. The choice between these techniques should consider individual patient characteristics and surgical expertise.
J Pediatr Surg. 2025 Jan;60(1):161974
Keywords: Anorectal malformation; Colostomy; Divided; Loop; Meta-analysis